JOOSTE, N.J.J. Inventory of documents - JOOSTE, N.J.J. (ARCA, 2018)
Private papers of N.J.J. Jooste, Private Secretary of Genl. Hertzog[1935], Ambassador in several countries [1946-1970].
COVERAGE 1900-1972; 5 Files; 0,11 Metre.
Keywords: JOOSTE, N.J.J.; Inventories; Politicians; National Party